Non-Traditional Crops, Traditional Constraints : The Adoption and Diffusion of Export Crops Among Guatemalan Smallholders - Carletto, Calogero; Kirk, Angeli; Winters, Paul; Davis, Benjamin (World Bank, Washington, DC, 2012)
This paper uses a duration analysis based on adoption data spanning more than 25 years from six communities in the Central Highlands of Guatemala. The analysis explores how household characteristics and external trends play into both the adoption and diffusion processes of non-traditional exports among smallholders. Adoption was initially widespread and rapid, which led nontraditional exports to be hailed as a pro-poor success, reaching all but the smallest landholders. However, over time more than two-thirds of adopters eventually dropped out of production of nontraditional exports. Based on the analysis, production of nontraditional exports appears to have delivered less prosperity to adopters than initially promised. Although smallholders may be enticed into entering into nontraditional exports markets when conditions are favorable, they may lack the capacity to overcome the difficulties that inevitably arise in complex types of cultivations and in highly variable global agricultural markets. Governmental and non-governmental organizations can attempt to mitigate these difficulties, but market forces may overwhelm their efforts, with some adopters still unable to compete in global markets.